Nodal mantle cell lymphoma: A descriptive study from a tertiary care center in South India - Arun Roy; Rakhee Kar; Debdatta Basu (Wolters Kluwer Medknow Publications, 2013)
Introduction: Mantle cell lymphoma (MCL) is a type of B-cell non-Hodgkin lymphoma (NHL) with distinctive morphologic, immunophenotypic and a characteristic cytogenetic abnormality, the t(11;14)(q13;q32) and overexpression of cyclin D1. The common histologic features include effaced lymphoid architecture by a monomorphic lymphoid population with a vaguely nodular, diffuse or mantle zone growth pattern. The classic cytomorphologic features include small to medium sized lymphoid cells with irregular nuclear contours and scanty cytoplasm, closely resembling centrocytes. Materials and Methods: This retrospective study comprises 13 cases of MCL over a period of 5½ years in our department, comprising 4% of all nodal NHL diagnosed. All cases were diagnosed on lymph node biopsy. Results: The mean age of the presentation was 57 years. There was a male preponderance (M:F = 2.25:1). The disease was nodal in all cases. Most patients (84.5%) had generalized lymphadenopathy and/or hepatosplenomegaly. Bone marrow involvement was seen in 81.8% of cases. Three cases showed a nodular pattern on lymph node biopsy while remaining ten had a diffuse pattern. Immunophenotyping showed positivity for CD20, CD5 and cyclin D1 and CD23 negativity. Conclusion: Despite certain morphological similarity to other low-grade/intermediate-grade lymphomas, MCL has a characteristic appearance of its own. Since it is more aggressive than other low-grade lymphomas it needs to be accurately diagnosed.